2010
DOI: 10.2478/v.10169-010-0017-6
|View full text |Cite
|
Sign up to set email alerts
|

Permeability of Sand-Clay Mixtures

Abstract: This study deals with the behavior of composite blends constituted of rigid and impervious grains included in saturated clay paste of kaolin, considered as permeable and deformable. Permeability tests performed during standard oedometr tests (before each load step) highlight the key role of the original and actual state of the clay paste, and show the existence of a threshold of sand grain concentration above which a structuring effect influences its permeability. In the light of these experiments some usual h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…(1). This formula is used for permeability prediction of clayey-sandy soils with a content of particles with a diameter d < 0.001 mm in an interval “a” between 2% and 20% (Kacprzak et al., 2010). This method was selected due to the fact that its assumptions can be met in the tested soils.…”
Section: Methodsmentioning
confidence: 99%
“…(1). This formula is used for permeability prediction of clayey-sandy soils with a content of particles with a diameter d < 0.001 mm in an interval “a” between 2% and 20% (Kacprzak et al., 2010). This method was selected due to the fact that its assumptions can be met in the tested soils.…”
Section: Methodsmentioning
confidence: 99%
“…(1). This formula is used for the permeability prediction of clayey sand, sandy silt and sandy clay with a content of particles with a diameter less than 1 μm in an interval “a” between 2% and 20% (Kacprzak et al., 2010). This method was selected due to the fact that its assumptions can be met in the tested soils.…”
Section: Methodsmentioning
confidence: 99%
“…Other studies showed that the mechanical behavior of sand-clay mixtures highly depends on mineralogical composition, mineral structure of clay, clay proportions, temperature, and hydrogeological characteristics [42][43][44][45][46][47][48][49][50][51][52][53][54]. Further studies have also investigated the effect of water content [34,55,56], the swelling properties and the suction distribution [34,55,57], the porosity and permeability [56,58], and the volume changes [36] on sand-clay mixtures, pointing out that each of them has non-negligible effects on the behavior of such mixtures.…”
Section: Definition Of Sand-clay Mixturementioning
confidence: 99%
“…Hence, the V v + V f is the volume of the intergranular void space. The intergranular void ratio provides an indicator of the influence of the granular phase [30,33,45,56]. It plays a role in the compressional stress-strain characteristics of soils consisting of fine and coarse grains of different percentages [50,75,83].…”
Section: Intergranular and Interfine Void Ratiosmentioning
confidence: 99%